No clear evidence of neuropathy among patients with high risk for the development of prediabetes/diabetes—a pilot study - Körei, Anna E.; Békeffy, Magdolna; Menyhárt, Adrienn; Osgyán, Karola; Istenes, Ildikó; Horváth, Viktor J.; Kempler, Péter (Frontiers in Endocrinology, 2024)
Introduction: Autonomic and sensory neuropathy have been observed in both prediabetes and manifest diabetes mellitus. However, there is a lack of available data regarding whether patients at a moderate or high risk of developing diabetes, yet without a current diagnosis of prediabetes or diabetes, exhibit an increased prevalence of neuropathy.Methods: FINDRISC score was used to classify individuals at risk (>/=12 points, n=44; control <12 points, n=28). HbA1c levels >5.6% served as exclusion criteria and patients with known medical conditions predisposing to neuropathy were also excluded. Cardiac autonomic function (Ewing tests) and peripheral sensory neuropathy (Neurometer and Qsense) were assessed by standardized protocols and their potential association with increased FINDRISC points was analysed using a regression model.Mean age was 46.7 ±14.3 years in the control and 55.7±14.1 years in the increased risk group. Male/female ratio did not differ. Individuals with increased risk of diabetes were more obese (BMI: 29.9 ± 12.5 kg/m2 vs. 25.9 ± 8.9 kg/m2). Additionally, hypertension was more frequent among them (68.2% vs 17.9%) and their lipid parameters were also less favourable. Parasympathetic neuropathy was present in both groups (56.8% vs. 32.1%, respectively). Sympathetic neuropathy was not found. Sensory nerve dysfunction was of low prevalence in the high-risk group and did not occur in healthy controls. In multiple logistic regression analysis, HbA1c exhibited an independent association with parasympathetic neuropathy (OR:5.9; 95%CI:1.08-32.68;p<0,041).Discussion: An increased risk of developing prediabetes/diabetes does not appear to have a strong correlation with an increased likelihood of developing autonomic or sensory neuropathy. However, the etiology behind the occurrence of parasympathetic autonomic neuropathy in healthy individuals remains unknown.